Assessment of the financial situation, determinants and the level of debt of seniors’ households - Zalega, Tomasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Population ageing is, on the one hand, a natural and inevitable process that occurs in every highly developed economy and, on the other hand, the biggest challenge for modern states, economies and entrepreneurs. This problem is beginning to affect Poland as well. Older people do not form a homogeneous group in terms of financial situation. Varying income levels of seniors’ households lead to marked differences also in the ways and purposes of spending money. Furthermore, such households also have an adverse structure of expenditure because of a small number of household members and a high proportion of fixed expenditure in the total spending. This article aims to assess the financial situation and the main causes and level of debt of seniors’ households. Secondary research results were also used in order to compare the author’s results with the research outcomes obtained by various research and scientific institutes.

Starzenie się społeczeństwa jest z jednej strony naturalnym i nieuniknionym procesem, który uwidacznia się w każdej wysoko rozwiniętej gospodarce, a z drugiej strony największym wyzwaniem dla współczesnego państwa, gospodarek i przedsiębiorców. Problem ten zaczyna być istotny również w Polsce. Starsze osoby nie stanowią grupy homogenicznej z punktu widzenia sytuacji finansowej. Zróżnicowane poziomy dochodów gospodarstw domowych osób starszych prowadzą do różnic rynkowych również w sposobach i celach wydatkowania pieniędzy. Co więcej, takie gospodarstwa domowe charakteryzuje również niekorzystna struktura wydatków ze względu na niewielką liczbę członków gospodarstwa oraz wysoki udział stałych wydatków w całkowitym ich poziomie. Celem artykułu jest ocena sytuacji finansowej oraz głównych przyczyn i poziomu zadłużenia gospodarstw domowych osób starszych. Dodatkowo, wyniki badań zostały także wykorzystane do porównania rezultatów otrzymanych przez autora z wynikami badań uzyskanymi w innych ośrodkach badawczych i naukowych.
Keywords: seniors; financial situation; debt; osoby starsze; sytuacja finansowa; zadłużenie